Depresi Pada Lansia Yang Tinggal di Griya Lansia dan Keluarga - Tantri Puspita; Eva Daniati; Muhammad Hadi Sulhan (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2023)
Introduction: The increase in the number of elderly will have a national impact. In terms of health, increasing age to elderly brings about many changes, one of which is psychological problems such as depression. Objective: This study aims was to compare the psychological conditions of elderly people in nursing homes and at family. Method: A comparative descriptive with secondary data was used to analyse the differences in levels of depression in the elderly. A total of 24 documents with clear demographic data and Geriatric Depression Scale (GDS) assessment results were taken for further analysis. Results: Most of the elderly in this study were male (50% in nursing homes, 67% at home). Most of the elderly are in the young elderly category (60-74 years) amounting to 88%, both nursing homes and living at home. The results of the GDS analysis show that more than 75% of elderly people experience mild depression. The Mann Whitney test shows that there is no difference in the level of GDS between elderly people at nursing homes and home with family (p> 0.05). Conclusion: the existence of the same conditions in the nursing homes causes the level of depression in the elderly to be no different from the elderly at home.